Multi-modalities in mobile technology for assisted learning performance in higher education in China - Yuan, Ruichen; Ab Jalil, Habibah; Omar, Muhd Khaizer (Multidisciplinary Digital Publishing Institute, 2025)
Mobile technology, especially mobile learning, has long been an emerging and thriving field, and remains a main theme in mobile learning applications and systems. The extensive utilization of mobile learning has prompted the invention of many mobile applications. As a result of rapid advances in application technologies, various learning applications can combine different media or multi-modalities, such as video, audio, images, animated graphics, and text, to create multimedia learning resources that engage learners. However, the most favorable modalities in different learning applications that assist performance are worth exploring. This study employed mixed methods to investigate the current multi-modality situation in learning application utilization among 300 university students in China, where a rapid educational technology revolution is occurring. The findings revealed that the verbal modality (M = 3.99, S*D = 0.79) and the writing modality (M = 3.99, S*D = 0.75) in the learning applications were less enjoyable and less effective at enhancing learning performance. In exam-based or function-based apps, all five modalities in this research were considered important, especially the visual and aural modes. The results of this study also revealed that a majority of university learners were satisfied with the multi-modalities in different types of applications, except for game-based apps, that assist their learning performance (56.7%, M = 3.87, S*D = 0.79), which contrasts with the results of several related studies. Overall, college users perceived that multi-modalities were effective in helping them to complete tasks, and all modalities in current applications satisfied most of the users’ needs to assist their learning performance. In the end, the findings indicated a positive and strong linear relationship [r = 0.766, p < 0.05] between multi-modalities and assisted learning performance with the help of more capable (knowledgeable) others with the use of mobile applications.